If $\alpha$, $\beta$, $\gamma$ are the roots of $x^3-4x^2+x+6=0$, find the equation whose roots are

1) $1/\alpha$, $1/\beta$, $1/\gamma$

2) $\alpha^2$, $\beta^2$, $\gamma^2$

How to do these kind of questions. I am stuck. I know,


$\alpha\beta+\beta \gamma+\alpha \gamma=c/a$

$\alpha \beta\gamma=-d/a$

  • $\begingroup$ These are not "quadratic roots". You should fix the title. $\endgroup$ – Yves Daoust Jun 20 '17 at 15:34

For the first one, set $x=1/y\implies$ $$\left(\dfrac1y\right)^3-4\left(\dfrac1y\right)^2+\left(\dfrac1y\right)+6=0$$

Multiply by $y^3$

For the second, $x^2=y,$

$$x(x^2+1)=4x^2-6\implies x(y+1)=4y-6$$

Square both sides and replace $x^2$ with $y$

  • $\begingroup$ Why did you put x=1/y @labbhattacharjee $\endgroup$ – onlymaths Jun 20 '17 at 15:29
  • $\begingroup$ They are just representing $x$ in a form more useful to answer the question. $\endgroup$ – fosho Jun 20 '17 at 15:32
  • $\begingroup$ @onlymaths, You can see the expected pattern of the roots $\endgroup$ – lab bhattacharjee Jun 20 '17 at 15:56

This equation can be factored as $(x + 1)(x - 2) (x -3)$. Let $\alpha = -1$, $\beta = 2$, and $\gamma = 3$. To find the equation with inverses of all of these, simply find the inverses and put them all together, such that you have $(x + 1)(x - 1/2)(x - 1/3)$. The same goes for the squares $(x - 1)(x - 4) (x-9)$.


for 1/alpha +1/beta +1/gamma just do sum of roots(2 at a time)/product of roots. For e.g. alphabeta+alphagamma+bettagamma/alphabetagamma

  • 1
    $\begingroup$ Please explain why. Also, take a look at using TeX to display formulae. $\endgroup$ – Rolazaro Azeveires Sep 9 '18 at 13:05
  • $\begingroup$ @Genius Your username doesn't come off as polite. Would you mind changing it? $\endgroup$ – Toby Mak Sep 9 '18 at 13:34

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.